L’impact de la création des agences d’exécution sur le Civil Service : décentralisation, marchandisation et conséquences constitutionnelles - Nicholas Sowels (Revue Française de Civilisation Britannique)
This article reviews the reforms of the Civil Service which have taken place since 1979 and the central role played by the creation of executive agencies. It analyses how the development of executive agencies along with the adoption of new management and governance practices have contributed to the emergence of a new model of Britain’s central government administration, characterised by a certain decentralisation and commodification of services. The article also analyses the constitutional consequences of these reforms.